The figurative nature of collocations: extent, knowledge and acquisition of duplex collocations by non-native speakers - Macis, Marijana (2016)
As shown by research conducted in the fields of corpus linguistics, psycholinguistics and second language acquisition (SLA), formulaic sequences (e.g. collocations, idioms, phrasal verbs, lexical bundles etc.) form a crucial part of second language learners’ language competence. One of the main characteristics of some of these multi-word combinations is their idiomatic nature and idioms have been widely researched as being the most compositional type. However, little is known whether collocations can be idiomatic too. Therefore, this thesis aims to fill that gap with a specific focus on statistically-derived collocations. Three studies have been carried out to this end. The first study examined the extent of collocations whose meanings were the sums of their component parts, those that were figurative (compositional or idiomatic) and finally, collocations that were polysemous, i.e. had both literal and figurative meanings. A corpus search was performed to find the most common V+N and Adj+N combinations and results showed that the majority of them had additive meanings (as reflected in traditional definitions of collocations), very few were completely opaque and a substantial percentage were those that allowed both literal and figurative interpretation. The second study was conducted in the Chilean classroom context and it focused on the knowledge of the figurative meanings of collocations. A meaning-recall test was used as a measurement instrument and variables such as corpus frequency, semantic transparency and language use factors were manipulated. The findings demonstrated rather weak figurative knowledge and a positive relationship between this knowledge and the amount of outside engagement. The last study investigated the same type of collocations, namely how non-native speakers acquired figurative meanings incidentally through reading. An authentic novel was used as a means to manipulate one single variable, frequency of exposure. Results showed that the figurative meanings could be acquired incidentally from reading and that the point at which a substantial amount of learning occurred varied greatly among individuals. Overall, results of the studies presented in this thesis stress the importance of researching the acquisition, use and knowledge of collocations with figurative meanings as they have important implications for instructed SLA.